Tax structure and revenue instability: The Great Recession and the states - Howard Chernick; Cordelia Reimers; Jennifer Tennant (IZA Journal of Labor Policy, 2014)
The Great Recession had the most severe impact on state tax revenues of any downturn since the Great Depression. We hypothesize that states with more progressive tax structures are more vulnerable to economic downturns, and that progressivity and income volatility may interact to amplify the recession's fiscal impact. We find that, while potential revenue exposure is greater in more progressive states, the most important source of variation was differences in income concentration and capital gains shares in the top 5 percent of taxpayers. Though the interaction between income volatility and high tax burdens at the top did produce large decreases in tax revenue in a few states, tax progressivity accounted for little of the overall interstate variation in revenue volatility.
Keywords: H24; H71; 330; Tax volatility; Tax progressivity; Income distribution; Capital gains